2015
DOI: 10.17765/2176-9168.2015v8n2p303-315
|View full text |Cite
|
Sign up to set email alerts
|

A Relação Peso-Comprimento e Fator de Condição para Carpa Capim (Ctenopharyngodon idella) Submetida a Diferentes Dietas

Abstract: RESUMO:Ctenopharyngodon idella, popularmente conhecida como carpa capim, é uma espécie exótica que vem sendo bastante apreciada devido ao seu desempenho na piscicultura. O presente estudo foi conduzido na estação de piscicultura da Universidade Estadual do Paraná, campus de União da Vitória, com o objetivo de avaliar o efeito de três diferentes tipos de alimentação no desenvolvimento de alevinos da carpa capim. Foi utilizado um lote inicial padrão de peso médio 13,0 ± 0,58 g e comprimento total 10,0 ± 0,10 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
1
1
Order By: Relevance
“…Results of the current study showed that growth is negative allometric before experiment and after the experiment, the growth in both treatments. This result is different from that of Riberio et al (2015) who recorded the existence of significant differences in this relationship for different treatments of grass carp in ponds.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of the current study showed that growth is negative allometric before experiment and after the experiment, the growth in both treatments. This result is different from that of Riberio et al (2015) who recorded the existence of significant differences in this relationship for different treatments of grass carp in ponds.…”
Section: Discussioncontrasting
confidence: 99%
“…Results of the present study is similar to that of Riberio et al (2015) with no significant differences for the condition coefficient between the different treatments. Nekoubin & Sudagar (2012) recorded a condition coefficient for jet plant of 0.9 and processed a ration of 0.8, which is less than what is recorded in the current study.…”
Section: Discussionsupporting
confidence: 84%
“…Dhanze & Dhanze (1997) studied the length-weight relationship of grass carp under the agro climatic zone of Himachal Pradesh. Wanner & Klumb (2009) studied the length-weight relationship and condition factor of three Asian carps in the Missouri River, while Riberio et al (2015) studied the length-weight relationship of C. idella fed on artificial diet, vegetable diet and mixed diet. Chitrakar & Parajuli (2017) showed that the relationship of length and weight of grass carp is important in the management of fish farming, which enables fish workers to know many things such as size, age and composition of the fish community as well as the health of the fishes, and that the relationship of length and weight in the same species may differ in fish populations because of feeding and fishing.…”
Section: Introductionmentioning
confidence: 99%